Design factors that influence the effective use of Meydan in Iran - Hajmirsadeghi, Reihaneh Sadat (2015)
This research addresses the issues of urban square as a public space, where less people are using the space for social interaction as well as participating in any event occurring in the square. Furthermore, most urban planners would just comply with the rules and regulations of the government's department in designing a public space and less consideration about the various needs of the public, especially with regards to social interaction. Consequently, the urban square lost its attraction and function as a public place. This research investigates the relationship between the design factors and effective use of public squares for social interaction in Qazvin, a town in Iran. Theoretical framework of this study was grounded by place, familiarity, hierarchy of human needs and personal construct theories. A quantitative and qualitative method based on a case study approach was employed in this study. A questionnaire survey was used for the quantitative part involving 208 respondents. The qualitative part involved 15 urban designers and architects for the in-depth interviews. The Structural Equation Modelling (SEM) and qualitative content analysis were used in data analysis. The data were triangulated to examine the relationships between the design factors and effective use of public squares for social interaction. The main theoretical contribution of this research is identifying the physical, managerial, geographical, behavioural and psychological design factors that influence the effective use of urban squares in the different geographical and cultural contexts. In addition, the type of activities generated within and surrounding the square has an influence in attracting people to use the square. The result also shows that, when people are satisfied with the design of public squares, they will be more involved in social activities occurring in the place. Theoretically, this study enhances the knowledge on design factors that influence social interaction in terms of effective use of public squares. The findings suggest that any decision to improve the public square should take into consideration the dominant function of the square as perceived by the users.